Development of a numerical optimization framework to identify optimal seismic resistant column jacketing configurations in low-rise buildings - Dhami, Sabita; Pennung Warnitchai; Krishna, Chaitanya; Anwar, Naveed; Computer and Structures Inc.(CSI), USA; AIT Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
This study presents a development of a numerical optimization framework for identifying the optimal column-jacketing strategy to enhance the seismic performance of a multi-story reinforced concrete structure.The work is focused on determining both the most effective locations of columns to be retrofitted with reinforced concrete (RC) jackets and the corresponding optimal jacket thicknesses using gradient-based numerical optimization technique. The case-study structure is a two-story building with an irregular arrangement of infilled walls in the ground floor, resulting in a soft-story condition.To improve computational efficiency, optimization is performed on two linear models with infill walls represented as equivalent struts using upper- and lower-bound elastic moduli,capturing both stiff and weak infill conditions.Three ground motions with short, moderate, and long predominant periods are considered. The framework begins with a stepwise optimization where multiple retrofit configurations are tested, followed by simultaneous optimization of column locations and jacket sizes using binary variables with a penalty function. A single retrofit scheme that satisfies constraints for all ground motions and both linear model variants is then selected.To evaluate the realism of linear-model-based optimization results, a nonlinear model is developed using the most effective solution and subjected to nonlinear time-history analysis.Comparing linear and nonlinear responses helps assess whether the linear-based optimum solution reflects true structural behavior.Overall, this study demonstrates a systematic and practical methodology for determining optimal column-jacketing configurations in multi-story buildings, contributing toward more reliable and faster seismic retrofit decision-making.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 2025
Keywords: Earthquake resistant design; Reinforced concrete construction; Columns, Concrete -- Testing